2018
DOI: 10.37358/mp.18.3.5014
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation Erosion Behavior on Thin Films of Polymer Blends Deposited Over Bronze Surfaces

Abstract: The composite materials with polymeric matrix represent a great realization of chemical engineering. Their applications in all the industrial fields are dictated by their chemical, physical and mechanical properties. In the last 50 years the polymeric composite materials received a large use in the protection and repair work of the surfaces in contact with fluid currents of various natures. The scientific researches followed by the industrial use, show that the polymere films with certain composition and prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The hoses were mounted as in figure 2 and external pressure was provided from a detachable high pressure compressor. The tested hose ( 2) is clamped into freely revolvable fixtures (1). Through an air tight seal air is pumped into the hose until de required pressure is obtained.…”
Section: Experimental Part Testing and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hoses were mounted as in figure 2 and external pressure was provided from a detachable high pressure compressor. The tested hose ( 2) is clamped into freely revolvable fixtures (1). Through an air tight seal air is pumped into the hose until de required pressure is obtained.…”
Section: Experimental Part Testing and Resultsmentioning
confidence: 99%
“…So, most vehicle encounter a fuel-line-related issues. Because of ethanol's effects on rubber, plastic and metals [1][2][3], there is a struggle in finding a solution that can offer a reliable delivery systems able to handle fuel in different mechanical conditions [4].…”
mentioning
confidence: 99%
“…Vasilescu [6] *email: alin_sirbu@yahoo.com, asirbu@isim.ro; sorin.ratiu@fih.upt.ro reported specific deviations of the obtained dimensions from the design, due to thermal expansion and contraction of the used material. Other results [12][13][14][15][16] showed that the semi-crystalline polymers present similar deformation behaviour (yielding, strain softening or hardening) as mainly of the amorphous polymers. Each modification influences the polymer behaviour during the 3D printing process.…”
Section: Additive Manufacturing General Principles Terminology 2017mentioning
confidence: 98%